Self-esteem and extraversion in predicting problematic smartphone use among Malaysian emerging adults - Lim, Edward Heng Yuan; Liew, Jia Kang; Yap, Jyh Shen (2019)
Emerging adults are said to be the most active group of smartphone users and were found to have high likelihood to engage in problematic use of smartphones. The present study sought to examine the relationship between self-esteem, extraversion and problematic smartphone use, as well as gender differences in problematic smartphone use among emerging adults in Malaysia. In this study, 343 participants were recruited using non-probability method of convenience sampling through online surveys distributed through various social media platforms. The results revealed that both self-esteem and extraversion significantly predicted problematic smartphone use, with self-esteem negatively predicted problematic smartphone use and extraversion positively predicted problematic smartphone use respectively. However, no significant gender difference was observed in problematic smartphone use among the emerging adults. Theoretically, the present study has contributed its new findings to the existing literature, especially in the Malaysian research context which was regarded as limited. In terms of practical contribution, the findings may be useful for mental health professionals and non-governmental authorities in their formulation of related modules and programmes to assist emerging adults who have problematic issues with smartphones. For future studies, it is recommended that qualitative or mixed methods of research to be conducted to further enhance the accuracy and reliability of the findings.